Historic American Building Survey Barter Island Long Range Radar Site Building Train "A" - 611th Civil Engineer Squadron (611th Air Support Group, United States Air Force, 2021)
This document includes a historic context and an architectural overview of Barter Island Long Range Radar Site Building Train "A." Barter Island LRRS was one of the original Alaska Distant Early Warning (DEW) Stations. The purpose of the DEW line was to constantly monitor for possible enemy aircraft and ballistic missile threats during the Cold War era. Building train “A” is representative of the modular DEW Line construction technique.